Characterization of plasma membrane associated type II α-d-mannosidase and β-N-acetylglucosaminidase of Aquarius remigis sperm. (May 2015) - Stephens, Kimberly; Thaler, Catherine D.; Cardullo, Richard A.
Abstract: For successful fertilization to occur, molecules on the surface of male and female gametes must recognize each other in a complementary manner. In some organisms, sperm possess a glycosidase on the plasma membrane overlying the head while eggs have glycoproteins that are recognized by those glycosidases resulting in sperm-egg recognition. In this study, two glycosidases, mannosidase and β-N-acetylglucosaminidase, were identified and biochemically characterized in Aquarius remigis sperm. The mannosidase had a Km of 2.36 ± 0.19 mM, a Vmax of 27.49 ± 0.88 pmol/min and a Hill coefficient of 0.94 ± 0.18 at its optimal pH of 7.0. The mannosidase was extracted most efficiently with CHAPSO but was also efficiently extracted with sodium chloride. Mannosidase activity was effectively inhibited by swainsonine, but not by kifunesine, and was significantly reduced in the presence of Mn 2+ and Mg 2+, but not Zn 2+ . N-acetylglucosaminidase had a Km of 0.093 ± 0.01 mM, a Vmax of 153.80 ± 2.97 pmol/min and a Hill coefficient of 0.96 ± 0.63 at its optimal pH of 7.0. N-acetylglucosaminidase was extracted most efficiently with potassium iodide but was also efficiently extracted with Triton X-100 and Zn 2+, but not Ca 2+, Co 2+, Mn 2+ or Mg 2+, significantly inhibited its activity. Taken together, these results indicate that the A. remigis sperm surface contains at least two glycosidases that may recognize complementary glycoconjugates on the surface of water strider eggs. Highlights: Aquarius remigis sperm surface GlcNAc'ase and α-mannosidase are cell surface enzymes. Neither β-N-acetylglucosaminidase nor α-mannosidase exhibit cooperative binding.